Optimization Development Dakwah on Dayah Salafiyah in the Regency Bireuen - Munawir, Munawir; Abdullah, Abdullah; Zainuddin, Darwin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2025)
This study aims to analyze the form development dakwah to the Salafiyah Dayah in the Regency Bireuen Aceh Province, consider existence and resilience Dayah in the Regency Bireuen reflect ability Dayah as institution preaching in face challenges of the times and remain relevant in the middle of social change. This matter has become an interesting thing because Dayah salafiyah is an example of a capable missionary institution responding to the challenges of the times with various innovative and relevant activities. ​ Study This includes a study qualitative in nature and descriptive with approach management preaching. Data collection techniques were used through observation, interviews, and documentation. Primary research data source This is interview data with the informant as Dai and Mad'u, who are leaders, servants, and teachers. Findings This explains form development preaching to the power salafiyah in the Regency Bireuen Aceh Province in terms of area, quantity, and quality in activity preaching. It covers routine study of the yellow book, cadre formation dai, formation organization preaching, opening college height and branches dayah, as well as use of social and electronic media. Dayah salafiyah tries to strengthen base religious scholarship and expand range preaching to the public.